Gambaran Kadar Asam Urat pada Mencit yang Diinduksi Minyak Jelantah dengan Variasi Pemanasan - Z, Khairunnisa; Sahputri, Juwita; Syifa, Refi; Sonia, Gina (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
Cooking oil is one of the basic needs of the community to meet their daily needs, especially as a source of fat. Based on the Food and Agriculture Organization (FAO) in 2015 consumption of vegetable oil as food material reached 19 kg/capita. The results of a survey conducted by the Indonesian Vegetable Oil Industry Association (GIMNI) in 2017 proved that producers and consumers of cooking oil reached 8.144 million tons. Waste cooking oil is oil derived from plants such as corn oil, vegetable oil and ghee that has been used as cooking oil. This oil is used oil for household use. Although it can be reused for economic reasons, for example for culinary purposes. However, when viewed from the chemical composition, used cooking oil contains carcinogenic compounds that occur during the frying process. The use of used cooking oil can interfere with the body's hemostasis, many disorders can be caused, it can increase cholesterol, blood sugar, uric acid and can even damage the intestinal villi and kidneys. There is a need for preliminary research on the description of uric acid levels due to used cooking oil which can be the basis for further research.